Creative Approaches to the Creation of Contemporary Art Objects and Features of their Legal Protection - Myronenko, Nataliia M.; Shtefan, Olena O.; Kedia, Yuliia O.; Derkach, Olha B.; Semeniuk, Kateryna O. (International Journal of Criminology and Sociology, 2021)
This study is devoted to the analysis of the current state of legislation of Ukraine and EU countries on copyright protection of works with an unstable form of expression, as well as to determine the features of the legal protection of such objects. The purpose of the article was to explore the existing possibilities in the law of Ukraine and the law of the EU countries for the protection of works with an unstable form of their expression. The article, based on the analysis of international legal acts and national legislation, highlights the elements of protection of works. A significant place in work is devoted to the analysis of theoretical, legislative approaches to the definition of "creativity", "originality", "novelty". It is stated that there is no single waste to the definition of these concepts in the literature and not regulated in the legislation in the field of copyright. A comparative legal analysis of the case-law of the United Kingdom and the United States on the provision of legal protection to works with an unstable form. It is concluded that the normative definition of “creative work”, which is associated exclusively with works of cultural value, is not acceptable for copyright. The article analyses the judicial practice of Ukraine, which has developed in the definition of creative work and illustrates its ambiguity. It is concluded that judges, considering such cases, try to find some stable elements that are inherent in works with an unstable form of expression.